Modeling of Non-Uniform Interference and Deformation Prediction for Riveting Assembly of Aircraft Thin-Walled Components - Yuanfan Hu; Yongguo Zhu (Aerospace)
Current deformation modeling theories for aircraft thin-walled components in riveting assembly typically assume uniform rivet interference. However, engineering practice shows that rivet interference is non-uniform, and such interference directly affects the magnitude of thin-walled component deformation during riveting assembly. Therefore, this paper investigates the deformation of aircraft thin-walled components caused by press riveting, models the non-uniform rivet interference for thin-walled components in riveting assembly, and conducts deformation prediction modeling. This paper performs stress analysis on the rivet shank to obtain the non-uniform distribution of riveting interference. Further, the non-uniform radial stress of the rivet shank and the bending moment of thin-walled components are derived. Using the thin plate theory, the deformation of aircraft thin-walled components in riveting assembly is calculated. The prediction model is applied to thin-walled component models with single-row and double-row riveting assemblies. Results show that the proposed prediction model is more accurate. Specifically, compared with traditional methods, the prediction accuracy of each index from this model is improved by over 29%.